Implementation of a Web-Based Media Partnership Registration Information System Using Waterfall Model - David Vernando Baridji; Alfiansyah Hasibuan; Medi H. Tinambunan (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
The Minahasa Regency Department of Communication and Informatics manages public information and cooperation with press media organizations, yet press media partnership registration is still handled manually. This causes processing delays, data duplication, limited traceability, and poor visibility of verification status, increasing administrative workload and reducing service transparency for applicants. This study implements a web-based Press Media Partnership Registration Information System to digitalize and standardize the registration workflow. Development follows the Waterfall model, including requirement analysis, system design, implementation, testing, and refinement to ensure structured deliverables suitable for government environments. The system provides CRUD-based data management, administrator-led verification with status tracking, and automated email notifications for verification outcomes. Functional validation uses Black Box Testing to evaluate input-output behavior against predefined specifications. Test results show that core modules—account registration, login, partnership submission, verification (approve/reject with notes), CRUD operations, session control, and email notification—operate correctly and meet functional requirements. The implemented system is feasible for operational use and improves efficiency, data accuracy, traceability, and transparency in local government press media partnership administration.